1987
DOI: 10.1128/jcm.25.2.268-272.1987
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of porcine pararotavirus and detection of virus and viral antibodies using cell culture immunofluorescence

Abstract: A cell culture immunofluorescence (CCIF) assay was optimized for detection of porcine pararotavirus (group C rotavirus) in intestinal contents. The greatest viral infectivity was observed when MAi04 cells (5 days after subculturing) were rinsed and refed in serum-free medium before inoculation, pancreatin was added to the inocula, and the inocula were centrifuged onto the cells. Gentamicin treatment of pararotavirus samples to reduce bacterial contamination also reduced the viral infectivity of these samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Based on limited serological surveys, we know that group C rotaviruses are widespread in pigs (2,19,22,26,28), suggesting that these infections may be endemic, like group A rotaviruses. In a limited survey of U.S. swine herds, Terrett et al (26) reported that about half of the 3-to 6-week-old pigs tested had group C antibodies and that all adult swine tested were positive for group C antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on limited serological surveys, we know that group C rotaviruses are widespread in pigs (2,19,22,26,28), suggesting that these infections may be endemic, like group A rotaviruses. In a limited survey of U.S. swine herds, Terrett et al (26) reported that about half of the 3-to 6-week-old pigs tested had group C antibodies and that all adult swine tested were positive for group C antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…(v) CCIF tests for the detection for group A and C rotavirus antigens. Confluent monolayers of MA104 cells in 96-well microplates were infected with the fecal samples diluted with minimal essential medium (MEM) (0.2 ml per well) as described previously (26). After incubation at 37°C for 20 h, the infected cells were washed with phosphate-buffered saline (pH 7.4) and fixed with 80% acetone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For detection, the virus has to be isolated in MA104 cell lines, similar to most of the mammalian rotaviruses. Diagonsis has also been facilitated by electron microscopy of diarrheic feces or immunofluorescence testing of tissue specimens (Terrett et al 1987). For differential diagnosis, recently, a multiplex RT-PCR has been developed which could ably differentiate porcine epidemic diarrhea virus, transmissible gastroenteritis virus and porcine group A rotavirus (Song et al 2006).…”
Section: Disease In Other Domestic Animalsmentioning
confidence: 99%
“…Fecal shedding of porcine GCRVs has been reported in nursing, weaning, and postweaning pigs with diarrhea either alone or in mixed infection with other enteric pathogens (Kim et al, 1999;Martella et al, 2007a;Morin et al, 1990;Saif and Jiang, 1994;Saif et al, 1980;Sigolo de San Juan et al, 1986). Moreover, porcine GCRVs are wide spread in swine herds; in limited surveys, antibody prevalence against GCRVs in pigs is 28-70% by 8 weeks of age, increasing with age to reach 79-100% in adult pigs (Saif and Jiang, 1994;Terrett et al, 1987;Tsunemitsu et al, 1992). However, the epidemiological significance of these observations is limited, given the limited number of studies and restricted geographical scope of such investigations (Collins et al, 2008;Janke et al, 1990;Kim et al, 1999;Martella et al, 2007a;Morin et al, 1990;Saif and Jiang, 1994;Saif et al, 1980;Sigolo de San Juan et al, 1986;Will et al, 1994).…”
Section: Introductionmentioning
confidence: 99%